The Role of School Student Organizations in Improving Character Education - sholahuddin irsyad; Isa Anshori (At-Tarbiyat, 2022)
This study understands the various roles that the School Student Organization performs in improving character education in Muhammadiyah Two Sidoarjo High School. Using qualitative research phenomenological approach premises. His research determined by purposive, namely the students who became an administrator and a member of student council. The type of data collected in the form of qualitative and quantitative primary and secondary sources. Analyzed by reduction, display and draw conclusions. To check the validity of the data is done tringulasi source. The results showed that the council has a major role in character education students. This is reinforced by the opinion of K.H. Dewantara about three things that underlie an education, firstly, family; secondly, the place of education; and thirdly, the youth movement. Then it resulted from this research that through various activities of the youth movement or student council. Through various activities the student council, the student's character becomes more intelijibel, ie, honest, disciplined, responsible, independent, confident, like mutual cooperation, leadership and creative spirit, and students can develop his potential and have creative ideas for the surrounding communities.